A non-noble metal oxide Ti2O3/rGO composite as efficient and highly stable electrocatalyst for oxygen reduction. (25th October 2019) - Shi, Yuande; Zhang, Yi; Zhang, Xiaofeng; Cai, Jiannan; Lin, Shen
Abstract: Developing low-cost and high-performance non-precious metal catalysts for oxygen reduction reaction (ORR) is highly desirable. Herein, the Ti2 O3 /reduced graphene oxide (Ti2 O3 /rGO) composite was successfully prepared by solid state synthesis. The electrochemical experiments indicated that the Ti2 O3 /rGO composite presents an excellent electrocatalytic activity and high selectivity for ORR via a four - electron pathway. Moreover, this composite also has outstanding durability and superior methanol tolerance compared with a commercial Pt/C catalyst in the alkaline (0.1M KOH) media. The superior ORR performance of Ti2 O3 /rGO composite may be ascribed to the low valence Ti, and the synergetic chemical coupling effects between Ti2 O3 and rGO. Graphical abstract: The Ti2 O3 /rGO with low valence Ti was synthesized by combination of agate ball-milling and heat treatment without adding any extra poisonous reductants. The Ti2 O3 /rGO composite exhibits efficient electrocatalytic activity and superior stability for ORR.Image 1 Highlights: Ti2 O3 /rGO were prepared by a solid state reaction process without extra reductants. The Ti2 O3 nanowire with low valence Ti is uniformly anchored on the rGO substrate. The Ti2 O3 /rGO exhibits efficient catalytic activity and superior stability for ORR. Synergistic reaction of Ti2 O3 and rGO is responsible for enhanced catalysis to ORR.